Problems of poverty of single-parent families in Tuva - Natsak, Organa D. (The New Research of Tuva, 2024)
The article analyzes the issue of poverty among single-parent families in the Republic of Tuva, where their numbers have been increasing in recent years. The study uses data from a sociological investigation conducted by the author in the region in 2023. Through in-depth interviews, 33 mothers heading single-parent families (monoparental households) were surveyed. It was found that single-parent families are at a higher risk of poverty compared to other family types. The primary source of income for these families is the wage of the mothers who head them. For various reasons, single-parent families often do not receive the full alimony to which they are entitled. Economic difficulties, the need for material and instrumental support from relatives, and the lack of their own housing compel some of these mothers to live with extended family. The role of subsistence farming as an adaptive strategy has diminished in importance. In rural areas facing high unemployment, government benefits have become a regular income source for single-parent families until children reach the age of 17. The article highlights that while government social transfers aimed at supporting single-parent families help reduce poverty levels within these households, they may also lessen the motivation for economic activity among women. The conclusion suggests that it would be advisable to classify single-parent families as a distinct group within the regional poverty reduction program. Recommendations are provided for targeted support of single-parent families as part of poverty alleviation measures.